2023
DOI: 10.1186/s40364-023-00499-0
|View full text |Cite|
|
Sign up to set email alerts
|

Oncofetal protein IGF2BPs in human cancer: functions, mechanisms and therapeutic potential

Abstract: N6-methyladenosine (m6A) is the most prevalent and well-characterized internal chemical modification in eukaryotic RNA, influencing gene expression and phenotypic changes by controlling RNA fate. Insulin-like growth factor-2 mRNA-binding proteins (IGF2BPs) preferentially function as m6A effector proteins, promoting stability and translation of m6A-modified RNAs. IGF2BPs, particularly IGF2BP1 and IGF2BP3, are widely recognized as oncofetal proteins predominantly expressed in cancer rather than normal tissues, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 129 publications
0
8
0
Order By: Relevance
“…4J ). IGF2BP3 was made up of two RNA recognition motifs (RRMs) and four K homology domains (KHs) [ 30 ]. Therefore, we established five FLAG-labeled full-length or fragmented IGF2BP3 plasmids and transfected them into the HEK293T cell line and verified them by western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4J ). IGF2BP3 was made up of two RNA recognition motifs (RRMs) and four K homology domains (KHs) [ 30 ]. Therefore, we established five FLAG-labeled full-length or fragmented IGF2BP3 plasmids and transfected them into the HEK293T cell line and verified them by western blot (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings indicate that the involvement of IGF2BP1/2/3, known as m6A readers, in the regulation of RNA stability plays a crucial role in tumor initiation, progression, and evolution. This disruption of normal expression and critical cellular signaling bioprocesses, including oncogenes and tumor suppressors, ultimately leads to the development and advancement of tumorigenesis [ 66 68 ]. In the present study, we identified a crucial regulatory network involving IGF2BP3 and altered HMGB1 through m6A modulation pattern, which is associated with BLCA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, including our own, have shown that IGF2BP3 is a cancer-causing factor and frequently exhibits high levels of expression in various types of cancer [ 68 ]. In a recent study, it was found that circNFATC3 has the ability to attach to IGF2BP3, resulting in an increase in the stability of IGF2BP3 by obstructing the ubiquitin E3 ligase TRIM25 from causing ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed crucial small compounds to specifically target the interactions between RBPs and RNA. These inhibitors mainly target the RNA Binding domains of RBPs which are crucial for RBP-RNA interactions such as the RNA-recognition motif (RRM), hnRNP K homology (KH), and the zinc-finger domain (268)(269)(270). These molecules serve as valuable tools for the development of innovative therapies aimed at inhibiting the function of RBPs.…”
Section: Small Molecule Inhibitors Designed For Targeting Rna Binding...mentioning
confidence: 99%